'It was Bauhaus without realising we were Bauhaus:' BBC women and Youth and Entertainment programming in the North. (September 2022) - Gorton, Kristyn; Helsby, Mark
This working paper focuses on women in leadership roles in the Entertainment Department of BBC North, based at New Broadcasting House on Oxford Road, Manchester and subsequently at Media City UK. In so doing, it considers the role of the department's founder, Janet Street-Porter, and her leadership of the then Youth Programmes department in the late 80s/early 90s. Drawing on interviews with six women professionals who worked either during or just after Street-Porter's leadership and scholarship on women in the UK media industry, this paper considers some of the reasons why this environment proved so fertile for our interviewees. We also reflect on some of the key issues the interviews provoked: the issue of balancing motherhood with a career in the UK television industry, the importance of women's networks, and the impact of class in terms of working in the BBC. In this sense, the BBC was formative for our interviewees, particularly through the leadership of an 'outsider' like Street-Porter despite structural issues of exclusion that remained present in the organisation.